2011
DOI: 10.3109/09638237.2011.583947
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on peer support in mental health services

Abstract: PSWs have the potential to drive through recovery-focused changes in services. However, many challenges are involved in the development of peer support. Careful training, supervision and management of all involved are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
811
0
45

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 889 publications
(893 citation statements)
references
References 47 publications
37
811
0
45
Order By: Relevance
“…Although not widely reported the theme of person-centeredness is implicit in the reviews of Carter (2011), Walker andBryant (2013), Lawton-Smith (2013) and Roberts and Boardman (2014) and being non-judgmental, a sub-theme (Figure 1) is advocated by Repper and Carter (2011). The other sub-themes of being informal, engaging, understanding, a non-pathological approach make up person-centeredness and together with accepting as cited in Repper and Carter (2011) makes this a term which can be used to remove any conflict when mentioning the recovery versus the medical model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not widely reported the theme of person-centeredness is implicit in the reviews of Carter (2011), Walker andBryant (2013), Lawton-Smith (2013) and Roberts and Boardman (2014) and being non-judgmental, a sub-theme (Figure 1) is advocated by Repper and Carter (2011). The other sub-themes of being informal, engaging, understanding, a non-pathological approach make up person-centeredness and together with accepting as cited in Repper and Carter (2011) makes this a term which can be used to remove any conflict when mentioning the recovery versus the medical model.…”
Section: Discussionmentioning
confidence: 99%
“…The other sub-themes of being informal, engaging, understanding, a non-pathological approach make up person-centeredness and together with accepting as cited in Repper and Carter (2011) makes this a term which can be used to remove any conflict when mentioning the recovery versus the medical model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top level finding is that peer-support is effective for reducing the feeling of self-stigma, increasing self-esteem, and agency 184,185,186 . However, improvement in clinical 179 For an overview focused on stigma impacts (and some mental health outcome impacts) see Hyman (2008) 180 (Frattaroli, 2006) 181 (Ellis and Cromby, 2011) 182 (Pavalanathan and De Choudhury, 2015) 183 (Joinson and Paine, 2007) 184 (Proudfoot et al, 2012) 185 (Cook et al, 2011) 186 (Repper and Carter, 2011) outcomes, such as hospitalization, has not been robustly demonstrated 187 . Additionally, there is evidence that the benefit of community support declines with increased severity of symptoms 188 .…”
Section: Community Identification and Support Help To Reduce Stigma Amentioning
confidence: 99%
“…In their review Repper and Carter (2011) identified a number of challenges in peer support work. These challenges include multiple Boundary issues such as being perceived as more of a friend to service users as a result of sharing personal information and experiences.…”
Section: Recommendations Regarding Implementation Of Peer Support Inimentioning
confidence: 99%